Association of preclinical blood glucose with hospitalization rate and in‐hospital mortality: A single‐center retrospective cohort study - Kloock, Simon; Skudelny, Danilo; Kranke, Peter; Güder, Gülmisal; Weismann, Dirk; Fassnacht, Martin; Ziegler, Christian G.; Dischinger, Ulrich (Journal of the American College of Emergency Physicians Open, 2024)
Critical illness is often accompanied by elevated blood glucose, which generally correlates with increased morbidity and mortality. Prehospital blood glucose (PBG) level might be a useful and easy‐to‐perform tool for risk assessment in emergency medicine. This retrospective single‐center cohort study was designed to analyze the association of prehospital glucose measurements with hospitalization rate and in‐hospital mortality. Records of 970 patients admitted to a university hospital by an emergency physician were analyzed. Patients with a PBG ≥140 mg/dL (G1, n = 394, equal to 7.8 mmol/L) were compared with patients with a PBG <140 mg/dL (G2, n = 576). Multivariable logistic regression models were used to correct for age, prediagnosed diabetes, and sex. Five hundred thirty‐four patients (55%) were hospitalized. In comparison to normoglycemic patients, hyperglycemic patients were more likely to be hospitalized with an adjusted odds ratio (OR) of 1.48 (95% confidence interval [CI] 1.11–1.97), more likely to be admitted to the intensive care unit (ICU) with an adjusted OR of 1.74 (95% CI 1.31–2.31) and more likely to die in the hospital with an adjusted OR of 1.84 (95% CI 0.96–3.53). Hospitalized hyperglycemic patients had a median length of stay of 6.0 days (interquartile range [IQR] 8.0) compared to 3.0 days (IQR 6.0) in the normoglycemic group (P < 0.001). In the subgroup analysis of cases without known diabetes, patients with PBG ≥140 mg/dL were more likely to be hospitalized with an adjusted OR of 1.49 (95% CI 1.10–2.03) and more likely to be admitted to ICU/intermediate care with an adjusted OR of 1.80 (95% CI 1.32–2.45), compared to normoglycemic patients. Elevated PBG ≥140 mg/dL was associated with a higher hospitalization risk, a longer length of stay, and a higher mortality risk and may therefore be included in risk assessment scores.